(untitled) (Eurasian Journal of Philology Science and Education, 2026)
The purpose of this article is to examine the concept of intercultural communication through the works of F. Dostoevsky, with particular attention to its reception by critics and writers of the American South. The relevance of this topic is determined by the fact that the socio-political and moral condition of post-reform Russia, including the state of the family in particular, was comparable to the destructive processes that took place in American society during the Civil War, Reconstruction, and the Great Depression. This similarity prompted American writers to turn to the literary legacy of the Russian classic, who depicted “Russian chaos” and the phenomenon of the “accidental family.” The article concludes that Dostoevsky saw the solution to the decline of the family and the crisis of morality and spirituality within the framework of Orthodox axiology, in faith in the Divine principle, universal human brotherhood, and the rejection of the destructive doctrine of bourgeois individualism. Writers of the American South also identified the cause of the disintegration of family ties in the dangerous isolation of the individual within the trajectory of the egoistic “self” and shared Dostoevsky’s view on the need for social empathy toward the weakest and most disadvantaged, especially the world of childhood. However, for American authors, the solution to this problem lay not in reliance on some Higher external force, but in the system of existential human values itself. In this regard, they called on their compatriots to demonstrate stoicism and individual courage in the most critical situations of private and social life. Keywords: intercultural communication, literary text, national identity, national reception, comparative-typological analysis.